Emotional distress and risk of dental caries: Evaluating effect modification by chronic conditions among low-income African American caregivers in Detroit, Michigan - Lim, Sungwoo; Tellez, Marisol; Ismail, Amid I. (Frontiers in Public Health, 2023)
Background/aim: Limited research has been conducted regarding the association between mental illness and dental caries. We studied the impact of emotional distress on current and new dental caries among low-income African-American caregivers in Detroit, Michigan and if this association was mediated by poor oral hygiene and sugar consumption and modified by a chronic health condition. Methods: Data came from Detroit Dental Health Project, a prospective cohort study of low-income African American caregivers and their children. We focused on baseline (n=1021) and 4-year follow-up participants (n=614). Dental caries were assessed using the International Caries Detection and Assessment System. The study outcomes included two baseline caries outcomes (counts of non-cavitated lesions, baseline counts of cavitated lesions) and two outcomes of new caries over 4 years (new cavitated lesions and new non-cavitated lesions). The exposure was emotional distress. We performed multivariable quasi-Poisson regression analysis to test the association between emotional distress and caries. We tested effect modification by stratifying data by chronic health conditions and performed causal mediation analysis to test an indirect effect of oral hygiene and sugar consumption. Results: Ninety six percent of the caregivers were female, and their average age was 28 years old. Thirteen percent reported emotional distress at baseline. After accounting for potential confounding, emotional distress was positively associated with cavitated lesions at baseline (IRR =1.36, 95% CI=1.08, 1.70). Among those with a chronic health condition, stronger association was observed (IRR = 1.73, 95% CI = 1.27, 2.35). After four years, those with emotional distress and chronic health conditions had an increased risk of developing non-cavitated carious lesions (IRR = 1.41, 95% CI = 1.06, 1.88). Poor oral hygiene explained 51% of the association between emotional distress and baseline cavitated lesions (natural indirect effect = 1.16, 95% CI = 1.02, 1.33), but there was no evidence for an indirect effect of sugar consumption. Conclusion: In this group of young, African-American caregivers with low socioeconomic status, dental caries was associated with emotional distress. This association was explained by poor oral hygiene and strengthened among those who reported a chronic health condition.